Synthesis, spectroscopic and computational studies of 2-(thiophen-2-yl)-2, 3-dihydro-1H-perimidine: An enzymes inhibition study. (October 2016) - Alam, Mahboob; Lee, Dong-Ung
Graphical abstract: Highlights: Experimental and theoretical spectroscopic analyses (FT-IR, UV, 1 H & 13 C NMR) of title compound. Theoretical IR frequencies are found in good agreement with IR experiments. Molecular properties like HOMO-LUMO analysis, NBO analysis, chemical reactivity descriptors. Enzyme inhibition study of the synthesized compound. Molecular docking and Hirshfeld analysis of intermolecular interactions. Abstract: The biologically relevant molecule; 2-(thiophen-2-yl)-2, 3-dihydro-1H-perimidine was synthesized and characterized by FT-IR, UV, 1 H and 13 C NMR, MS, CHN microanalysis, X-ray crystallography as well as by theoretical, B3LYP/6-311++G(d, p), calculations. The vibrational bands appearing in the FT-IR were assigned with great accuracy using animated modes. Molecular properties like HOMO–LUMO analysis, chemical reactivity descriptors, MEP mapping, dipole moment and natural charges have been presented at the same level of theory. The theoretical results are found in good correlation with the experimental data obtained from the various spectral techniques. Moreover, the Hirshfeld analysis was performed to explore the secondary interactions and associated 2D fingerprint plots. Perimidine molecule displayed promising inhibitory activity against acetylcholinesterase (AChE) as compared to the reference drug, tacrine. Molecular docking was carried out to ascertain the synthesized molecule into the X-ray crystal structures of acetylcholinesterase at the active site to find out the probable binding mode. The results of molecular docking admitted that perimidine may reveal enzyme inhibitor activity.